Egyptian Journal of Forensic Sciences - Kharoshah, Magdy A.
Egyptian Journal of Forensic Sciences, the official publication of The International Association of Law and Forensic Sciences (IALFS), is an open access journal that publishes articles in the forensic sciences, pathology and clinical forensic medicine and its related specialities. The journal carries classic reviews, case studies, original research, hypotheses and learning points, offering critical analysis and scientific appraisal.